Readiness of Water Sanitation and Hygiene Facilities (WASH) as an Effort to Prevent COVID-19 Transmission in Elementary Schools at Ngaliyan District, Semarang City - Yudhana, Ega Friesa; Siwiendrayanti, Arum (Journal of Public Health for Tropical and Coastal Region, 2022)
Introduction: Ngaliyan sub-district on Semarang city has the highest cases of Covid-19 (212 cases) in July 2021. High proportion of them occurred on elementary school-aged children aged 7-12 years. Among other levels of education, this group also has the lowest levels of sanitation. This study aimed to determine the readiness of WASH facilities as an effort to prevent the transmission of COVID-19 in elementary schools at Ngaliyan Sub-District, Semarang City.Methods : This study was a descriptive observational study. Data collection techniques were carried out by observation, on 36 elementary schools in Ngaliyan District (total sampling method). Readiness of Water Sanitation and Hygiene Facilities (WASH) in each school were observed using checklist. Data were classified and compared to the requirements.Results: The results of this study indicate that 100% of primary schools in Ngaliyan sub-district have the readiness of WASH facilities. Of the 36 primary schools, 97% of schools met the requirements for clean water, 64% for the toilet conditions, 14% for the waste disposal and 100% of the waste water disposal system and 67% for the hand washing facilities.Conclusion: In general, WASH facilities in the elementary schools in Ngaliyan Sub district was ready for the transmission of COVID-19 prevention, but some improvements should be done, especially for the waste disposal, toilet conditions and hand washing facilities.